Identification of SSR Markers Associated with Northern Corn Leaf Blight Resistance in Sweet Corns - Wongwarat, Theerawut; Kerdsri, Chalong; Phruetthithep, Chaowanart (Thai Agricultural Research Journal, 2024)
Northern corn leaf blight (NCLB) caused by Exserohilum turcicum, is one of the most serious diseases of sweet corn. Resistant variety is often considered the most effective method for controlling NCLB. Conventional breeding for developing sweet corn resistant to NCLB is time-consuming and the evaluation of NCLB resistance in sweet corn is influenced by environmental conditions. Utilising DNA markers to screen for resistance to NCLB in sweet corn is less time consuming and more effective. This research focused on identifying 16 SSR markers that could be associated with polymorphisms related to NCLB disease reaction. Twenty-six commercial sweet corn cultivars/hybrids were used in this study. Results indicated that SSR marker, bnlg182, located on chromosome 1 (bin no. 1.03), exhibited different particular alleles between moderately resistant and moderately susceptible to NCLB disease. Then the bnlg182 marker was used as the template for amplification of the DNA of 158 S6 lines of sweet corn. The presence of particular alleles related to resistance to NCLB from 10 S6 lines of sweet corn. These sweet corn lines were planted to evaluate their resistance to NCLB disease. The results indicated that the 10 S6 lines of sweet corn exhibited a moderate resistance (19 -30%) to NCLB disease. The utilisation of the bnlg182 marker as a screening tool in resistance sweet corn breeding programs offers the advantages of being simple and fast.